Macro- and microelements of blood mononuclear leukocytes in patients withpulmonary tuberculosis - V. V. Novitsky; A. K. Strelis; O. I. Ourazova; T. A. Shilko; S. B. Tkachenko; I. Ye. Yesimova; O. V. Voronkova; V. A. Serebryakova; O. V. Filinyuk; Ye. V. Ivanova; O. V. Baranova (Бюллетень сибирской медицины)
In article the results of the analysis of changes of the contents macro- and microelements (К+, Ca2+, Fe2+, Cu2+, Mn2+, Zn2+, Mg2+, Al3+) in lymphocytes and monocytes of peripheral blood in patients with infiltrative drug-sensitive and drug-resistant pulmonary tuberculosis before and on a background of realization standard antituberculosis therapy are discussed